Improvements in fracture behavior and shear capacity of fiber reinforced normal and self consolidating concrete: A comparative study. (20th November 2018) - Gali, Sahith; Subramaniam, Kolluru V.L.
Highlights: Fracture and shear behaviors of SCC and NC with the addition of steel fibers are compared. Significant tensile post cracking resistance and higher crack closing cohesive stresses are produced in steel fiber reinforced SCC when compared with normal concrete. Displacements measured across the shear crack indicate a continuous dilatant crack opening displacement produced by slip between the crack faces. There is a larger increase in shear capacity of SCC with the addition of fibers than the corresponding increase in normal concrete. The relative increases in the shear capacity of NC and SCC with the addition of steel fibers are consistent with the relative increases in the tensile fracture energies. Abstract: Flexural fracture and shear behaviors of self-consolidating concrete (SCC) and normal concrete (NC) with 0.75% volume fraction of hooked-end steel fibers are evaluated and compared. The cohesive stress-crack separation behavior obtained from the fracture test indicates that the steel fibers are significantly more effective in providing crack control in SCC than in NC. A significantly larger crack closing stress is generated in steel fiber reinforced SCC (SFSCC) even at small crack opening when compared with steel fiber reinforced normal concrete (SFNC). The fracture energy of SFSCC obtained from flexure tests is higher than the fracture energy of SFNC. In the shear response of reinforced concrete, there is a significantly larger increase in the shear capacity of SCC with the addition of fibers when compared with relative increase in NC with the addition of fibers. Full-field displacements obtained from Digital Image Correlation (DIC) is used to establish the in-situ dilatant behavior of the shear crack. The displacements measured across the primary shear crack indicates a continuous increase in the relative slip accompanied by an increase in the crack opening. The dilatant response measured in SCC indicates a smaller crack opening displacement resulting from slip across the primary shear crack when compared with normal concrete. In both NC and SCC, the shear capacity is determined by the failure of stress transfer across the shear crack. Shear failure in SCC occurs at a small crack opening, less than 0.1 mm whereas in NC it occurs at an opening of around 1.0 mm. With the addition of fibers, there is an increase in the load carrying capacity and the load transfer across the primary shear crack is sustained for a larger crack opening in both NC and SCC. The shear stress transfer across the primary shear crack in SFSCC is sustained for a crack opening up to 1 mm. The increase in the crack closing stress provided by steel fibers in SCC matrix contributes to an increase in the shear capacity through better crack control, which results in better shear stress transfer characteristics. The relative increases in the shear capacity of NC and SCC with the addition of steel fibers are consistent with the relative increases in the fracture energies.